14. 128
15.25
16.90
those should be right
36+10=46
=46
(20 characterssss)
let's set up an equation:
x-4=9
solve normally:
x=13
Answer:
a. Variable term
b. Variable term
Explanation:
a) We were given the algebraic expression:
![-5y-6b](https://tex.z-dn.net/?f=-5y-6b)
The first term of the algebraic expression is:
![-5y](https://tex.z-dn.net/?f=-5y)
The first term is a variable term
The variable is "y" and its coefficient is "-5"
b) We were given the algebraic expression:
![-5y-6b](https://tex.z-dn.net/?f=-5y-6b)
The second term of the algebraic expression is:
![-6b](https://tex.z-dn.net/?f=-6b)
The second term is a variable term
The variable is "b" and the coefficient is "-6"